A comprehensive review on renewable and sustainable heating systems for poultry farming. (20th November 2019) - Cui, Yuanlong; Theo, Elmer; Gurler, Tugba; Su, Yuehong; Saffa, Riffat
Abstract: Poultry farming is one of energy intensive industries that consume large amount of energy to provide the suitable indoor environment for chicken health and production like meat and eggs. Currently, there are extensive researches and practices of applying renewable and sustainable energy technologies to poultry farming to achieve energy saving and carbon dioxide emission reduction. Therefore, it is worth to retrospect the state-of-the-art development and summarize the key features in this field. The main technologies include photovoltaic (PV), solar collector, hybrid PV/Thermal, thermal energy storage, ground/water/air sources heat pumps, lighting and radiant heating. It is found that up to 85% energy saving can be achieved by using these advanced technologies in comparison to the traditional poultry houses with a payback time of 3–8 years.